Layering of a health, nutrition and sanitation programme onto microfinance-oriented self-help groups in rural India: results from a process evaluation - Laili Irani; Janine Schooley; Supriya; Indrajit Chaudhuri (BMC, 2021)
Abstract Background The state of Bihar has been lagging behind Indian national averages on indicators related to maternal and child health, primarily due to lack of knowledge among mothers of young children on lifesaving practices and on where to seek services when healthcare is needed. Hence, the JEEViKA Technical Support Programme was established in 101 blocks to support the state rural livelihood entity, JEEViKA, in order to increase demand for and link rural families to existing health, nutrition and sanitation services. Programme activities were geared to those engaged in JEEViKA's microfinance-oriented self-help groups. These groups were facilitated by a village-based community mobilizer who was trained on health, nutrition and sanitation-related topics which she later shared in self-help group meetings monthly and during ad hoc home visits. Further, a block-level health, nutrition and sanitation integrator was introduced within JEEViKA to support community mobilizers. Also, indicators were added into the existing monitoring system to routinely capture the layering of health, nutrition and sanitation activities. Methods A process evaluation was conducted from August-November 2017 which comprised of conducting 594 quantitative surveys with community mobilizers, from program and non-programme intervention blocks. Linear and logistic regressions were done to capture the association of at least one training that the community mobilizers received on knowledge of the topics learned and related activities they carried out. Results Community mobilizers who had received at least one training were more likely to have higher levels of knowledge on the topics they learned and were also more likely to carry out related activities, such as interacting with block-level integrators for guidance and support, routinely collect data on health, nutrition and sanitation indicators and spend time weekly on related activities. Conclusions Successful integration of health, nutrition and sanitation programming within a non-health programme such as JEEViKA is possible through trainings provided to dedicated staff in decentralized positions, such as community mobilizers. The findings of this evaluation hold great promise for engaging existing non-health, nutrition and sanitation systems that are serving vulnerable communities to become partners in working towards ensuring stronger health, nutrition and sanitation outcomes for all.